Ultrasound-Induced Destruction of Nitric Oxide–Loaded Microbubbles in the Treatment of Thrombus and Ischemia–Reperfusion Injury - Liang, Zenghui; Chen, Huafang; Gong, Xuehao; Shi, Binbin; Lin, Lili; Tao, Fangyi; Wu, Qilong; Fang, Mingling; Li, Hui; Lu, Cuitao; Xu, Helin; Zhao, Yingzheng; et al. (Frontiers in Pharmacology, 2022)
Abstract Objectives: Early recanalization of large vessels in thromboembolism, such as myocardial infarction and ischemic stroke, is associated with improved clinical outcomes. Nitric oxide (NO), a biological gas signaling molecule, has been proven to protect against ischemia-reperfusion injury (IRI). However, the underlying mechanisms remain to be explored. This study investigated whether NO could mitigate IRI and the role of NO during acoustic cavitation. Methods: In vivo, thrombi in the iliac artery of rats were induced by 5% FeCl3. NO-loaded microbubbles (NO-MBs) and ultrasound were used to treat thrombi. B-mode and Doppler ultrasound and histological analyses were utilized to evaluate the thrombolysis effect in rats with thrombi. Immunohistochemistry, immunofluorescence and western blotting were conducted to investigate the underlying mechanisms of NO during acoustic cavitation. In vitro, hypoxia was used to stimulate cells, and NO-MBs were employed to alleviate oxidative stress and apoptosis. Results: We developed an NO-MB that significantly improves the circulation time of NO in vivo, is visible and effectively releases therapeutic gas under ultrasound. Ultrasound-targeted microbubble destruction (UTMD) and NO-loaded ultrasound-targeted microbubble destruction (NO+UTMD) caused a significant decrease in the thrombus area and an increase in the recanalization rates and blood flow velocities compared to those of the control and ultrasound groups. We discovered that UTMD induced NO generation through activation of endothelial nitric oxide synthase (eNOS) in vivo. More importantly, we also observed a significantly increased NO content and eNOS expression in the NO+UTMD group compared to the UTMD group. NO+UTMD can mitigate oxidative stress and apoptosis in hindlimb muscle without influencing blood pressure or liver and kidney function. In vitro, NO-MBs alleviated oxidative stress and apoptosis in cells pretreated with hypoxia. Conclusions: Based on these data, UTMD affects the vascular endothelium by activating eNOS, and NO exerts a protective effect against IRI.